PSYCHOSOMATIC RELATIONSHIPS IN PATIENTS WITH BRONCHOPULMONARY PATHOLOGY - L.U. Zakirova (International Scientific and Current Research Conferences, 2023)
This article discusses the psychosomatic relationships in patients with bronchopulmonary pathology. The study involved 68 patients of the pulmonology department of the city clinical hospital of the city of Bukhara. The technique for determining the level of neuroticism and psychopathization (LNP) was used.